Comprehensive evaluation of body composition in a wide age range of Iranian adults using bioelectrical impedance analysis: Tehran Lipid and Glucose Study - Mahdieh Mohamadzadeh; Majid Valizadeh; Farhad Hosseinpanah; Amirabbas Momenan; Maryam Mahdavi; Maryam Barzin; Feridoun Azizi (Cambridge University Press, 2024)
Abstract Objective: To evaluate sex- and age-stratified body composition (BC) parameters in subjects with wide age range of 20-79 years. Design: Cross-sectional. Setting: Participants of Tehran Lipid and Glucose Study (TLGS). Participants: Two thousand nine hundred seventy participants met our inclusion criteria. They were divided into five age groups, and BC parameters were analysed based on sex and age using a bioelectrical impedance analyser (BIA). Result: The mean age of the participants was 42·1 ± 12·5 years, and 54 % of them were males. The mean BMI was 26·7 ± 3·7 kg/m2. Obesity indices were significantly higher in females (P < 0·001); however, skeletal muscle mass (SMM) and fat-free mass (FFM) were significantly higher in males (P < 0·001). Both SMM and FFM decreased significantly after the age of 50 years. Obesity indices significantly increased from the age group of 20-29 to 30-39 years in males and the age groups of 30-39 to 40-49 years and 40-49 to 50-59 years in females. The fat mass ratio (fat mass/SMM) showed two peaks in both sexes (after the ages of 30 and 50 years in males and 40 and 50 years in females). A strong correlation was found between BMI and percentage of body fat (r = 0·823 in females v. r = 0·768 in males). Conclusion: This is the first community-based study in the MENA region identifying sex- and age-stratified BC values using BIA. Our findings can be used as a reference for comparison in appropriate settings.